## Active forum topics

- Eliminate the Arbitrary Constants
- Law of cosines
- Maxima and minima (trapezoidal gutter)
- Special products and factoring
- Integration of 4x^2/csc^3x√sinxcosx dx
- application of minima and maxima
- Sight Distance of Vertical Parabolic Curve
- Application of Differential Equation: Newton's Law of Cooling
- Minima maxima: a²y = x⁴
- Trim and stability

## New forum topics

- Integration of 4x^2/csc^3x√sinxcosx dx
- Maxima and minima (trapezoidal gutter)
- Special products and factoring
- Newton's Law of Cooling
- Law of cosines
- Can you help me po to solve this?
- Eliminate the Arbitrary Constants
- Required diameter of solid shaft
- Differentiate trigonometric function
- Integration $\displaystyle \int \sec 2x ~ dx$

## Recent comments

- Mali po ang equation mo…3 days 6 hours ago
- $x$ is the location where…3 days 17 hours ago
- In double integration method…1 week 1 day ago
- Maayo, salamat sa imong…2 weeks 3 days ago
- 24 ft during the 10th second…2 weeks 3 days ago
- The differentiation you need…2 weeks 4 days ago
- Obtain the differential…2 weeks 4 days ago
- Thank you for sharing your…2 weeks 4 days ago
- Based on the differentiation…1 week 1 day ago
- Given that $x + y + xy = 1$,…1 week 1 day ago

## Re: analytic geometry

Center (h, k)

$2h - 18k = -25$

$k = \dfrac{2h + 25}{18}$

Distance from (h, k) to 2x + y = 1

$d_1 = \dfrac{2h + k - 1}{\sqrt{2^2 + 1^2}}$

$d_1 = \dfrac{2h + k - 1}{\sqrt{5}}$

Distance from (h, k) to 2x + 4y = 3

$d_2 = \dfrac{2h + 4k - 3}{\sqrt{2^2 + 4^2}}$

$d_2 = \dfrac{2h + 4k - 3}{2\sqrt{5}}$

Radius of circle r = d

_{1}= d_{2}$d_1 = d_2$

$\dfrac{2h + k - 1}{\sqrt{5}} = \dfrac{2h + 4k - 3}{2\sqrt{5}}$

$2(2h + k - 1) = 2h + 4k - 3$

$2h - 2k + 1 = 0$

$2h - 2\left( \dfrac{2h + 25}{18} \right) + 1 = 0$

$18h - (2h + 25) + 9 = 0$

$h = 1$

$k = \dfrac{2(1) + 25}{18}$

$k = \frac{3}{2}$

$r = \dfrac{2(1) + \frac{3}{2} - 1}{\sqrt{5}}$

$r = \frac{1}{2}\sqrt{5}$

Equation of the circle

$(x - h)^2 + (y - k)^2 = r^2$

$(x - 1)^2 + (y - \frac{3}{2})^2 = (\frac{1}{2}\sqrt{5})^2$

$(x^2 - 2x + 1) + (y^2 - 3y + \frac{9}{4}) = \frac{5}{4}$

$x^2 + y^2 - 2x - 3y + 2 = 0$

## Re: analytic geometry

thank you po!